2011
DOI: 10.1063/1.3596748
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Rovibrationally selected study of the N2+(X; v+ = 1, N+ = 0−8) + Ar charge transfer reaction using the vacuum ultraviolet laser pulsed field ionization-photoion method

Abstract: Rovibrationally selected ion-molecule collision study using the molecular beam vacuum ultraviolet laser pulsed A vacuum-ultraviolet laser pulsed field ionization-photoelectron study of sulfur monoxide (SO) and its cation (SO +

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…The H 2 O beam thus formed traveled along the central axis of the DQDO apparatus, and intersected the VUV laser beam at the photoionization/photoexcitation (PI/PEX) region, resulting in the formation of prompt H 2 O + ions as well as excited H 2 O*(n ≈ 100) in high-n Rydberg states. By employing the pulsing scheme to the PI/PEX region as that described previously in detail, 15,16 we were able to generate a rovibrationally selected…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The H 2 O beam thus formed traveled along the central axis of the DQDO apparatus, and intersected the VUV laser beam at the photoionization/photoexcitation (PI/PEX) region, resulting in the formation of prompt H 2 O + ions as well as excited H 2 O*(n ≈ 100) in high-n Rydberg states. By employing the pulsing scheme to the PI/PEX region as that described previously in detail, 15,16 we were able to generate a rovibrationally selected…”
mentioning
confidence: 99%
“…15,16 Since the H 2 O + reactant ions react with D 2 in the reaction gas cell, the E cm value for the present cross section measurement depends not only on the E lab value for the reactant ion beam, but also the thermal motion of the D 2 gas in the gas cell at the temperature T = 298 K. Chantry has shown that the E cm value or the Doppler width caused by the thermal motion of the target gas alone is W 1/2 = (11.1γ kTE cm ) 1 Figs. 1(a) and 1(b), respectively.…”
mentioning
confidence: 99%
See 3 more Smart Citations